Communicating accurate and complete information. (January 2018) - Levy, David T.
Highlights: Consumers should be provided with the best information about the risks of different tobacco products to make informed choices. However, better information is needed about effectively communicating relative as well as absolute risks. In particular, studies are needed on communicating the risks of dual use.